Home computing unplugged: why, where and when people use different connected devices at home - Kawsar, Fahim; Brush, A.J. (UbiComp '13 Proceedings of the 2013 ACM international joint conference on Pervasive and ubiquitous computing., 2013)
We investigate how technology usage in homes has changed with the increasing prevalence of mobile devices including Tablets and Smart Phones. We logged Internet usage from 86 Belgium households to determine their six most common Internet Activities. Next, we surveyed households about what devices they own, how they share those devices, and which device they use for different Internet activities. We then conducted semi-structured interviews with 18 of 55 households that responded to the survey in which participants explained their device usage patterns and where they use technology in their home. Our findings suggest that the nature of online activity and social context influence device preference. Many participants reported that their Desktop PC is now a special purpose device, which they use only for specific activities such as working from home or online gaming. Compared to past studies, we observed technology use in many more locations in the home, most notably kitchens and bathrooms.